Innovation and productivity: evidence from firms level data on Malaysian manufacturing sector - Shafi’i, Mazlina; Ismail, Normaz Wana (Faculty of Economics and Management, Universiti Putra Malaysia, 2015)
This study aims to investigate the impact of innovative activities related to productivity among firms in Malaysian manufacturing sector, using cross section data in 2008 with the total number of observations is 7222 firms from 36 manufacturing sub-sectors. The link between R&D, innovation and productivity has been examined through a complex interaction via the structural model. The results reveal that, exportoriented firms, size of firm, type of industry and market size heavily influence the decision to engage in R&D and at the same time firm allocates some significant amount of expenditure for R&D. The result also support that exporting firms tend to innovate to enhance their product competitiveness globally and patent their products worldwide as a form of protection from imitation. In addition, the innovation activities with the support of quality labor and technology are able to trigger firm’s productivity.